Preparing our future workforce: a qualitative exploration of dietetics practice educators' experiences. Issue 2 (21st January 2019) - Morgan, K.; Campbell, K. L.; Sargeant, S.; Reidlinger, D. P.
Abstract: Background: Dietetics practice educators are instrumental in the development of future dietitians. The present study aimed to explore dietetics practice educators' experiences of, and challenges faced in, dietetics workforce preparation. Methods: This study was guided by interpretive description methodology. Purposive and maximum variation sampling were used to recruit 18 dietetics practice educators from a variety of practice areas and locations across Australia. In‐depth, semi‐structured interviews were digitally recorded then transcribed verbatim and inductive coding of data was managed withnvivo (QSR International Pty Ltd, Doncaster, VIC, Australia). Multiple researchers analysed the data to develop preliminary themes using template analysis before final themes were identified. Results: Three main themes were developed: nurturing others; seeing the flaws; and soldiering on. Practice educators take great satisfaction in witnessing students develop and are focused on cultivating future practitioners with authentic learning activities. However, they are impacted by perceived shortcomings of the systems in which they operate and consider that broadening the scope of dietetics placements to better align with contemporary practice could benefit graduates and the profession. Despite these challenges, practice educators are pragmatic in getting on with their roles and recognise the advantages gained from student placements. Conclusions: Despite facing numerous challenges, practice educators derive benefits from their role in workforce preparation. Evidence is required on how students can demonstrate competence in contemporary areas of practice and on how to enable the scope of student placements to be broadened. Such strategies could support practice educators to overcome challenges and help ensure the dietetics profession of tomorrow is relevant and responsive.